Long Non-Coding RNA MAFG-AS1 as a Potential Biomarker for Hepatocellular Carcinoma: Linkage with Tumor Features, Markers, Liver Functions, and Survival Profile - Tian, Yuanyuan; Wang, Jiao; Tian, Ge; Li, Bing; Chen, Moli; Sun, Xiaoning (Frontiers in Surgery, 2022)
Purpose: Long non-coding RNA MAFG-AS1 (lnc-MAFG-AS1) regulates hepatocellular carcinoma (HCC) progression and treatment resistance in multiple ways, while its engagement in HCC clinical management is still obscure. The current study aimed to explore the relation of lnc-MAFG-AS1 with tumor features, liver function indexes, tumor markers, and prognosis in HCC patients. Methods: One hundred and fifty-two surgical HCC patients who underwent tumor resection were retrospectively analyzed. Their tumor and adjacent tissues were acquired and then proposed to reverse transcription-quantitative polymerase chain reaction to detect lnc-MAFG-AS1 expression. Results: Lnc-MAFG-AS1 expression was increased in HCC tumor tissue compared to adjacent tissue (median (interquartile range): 2.730 (1.685-4.198) vs. 0.990 (0.703-1.468), P<0.001), with a high area under the curve (0.889, 95%CI: 0.854-0.924) to distinguish them via receiver operating characteristic curve analysis. Tumor lnc-MAFG-AS1 was linked with multifocal nodules (P<0.001), increased Barcelona Clinic Liver Cancer (BCLC) stage (P=0.018) and elevated China Liver Cancer (CNLC) stage (P=0.008), which also correlated with abnormal alpha-fetoprotein (AFP) level (P=0.004), However, lnc-MAFG-AS1 was not linked with other disease conditions, tumor properties, liver function indexes or tumor markers (all P>0.05). In addition, patients with lnc-MAFG-AS1 high expression exhibited worse OS compared to those with lnc-MAFG-AS1 low expression (median (95%CI): 34.0 (24.5-43.5) vs. 48.0 (41.5-54.5) months) (P=0.011), which was further validated by univariate Cox’s analysis (HR=1.827, P=0.013) and multivariate Cox’s analysis (HR=1.697, P=0.040). Conclusion: Lnc-MAFG-AS1 relates to multifocal nodules, increased BCLC stage, elevated CNLC stage, abnormal AFP level, and predicts pejorative prognosis in HCC patients.